Bringing writing and drawing back together - Ramos, M. (Morgan Centre seminar - University of Manchester, 20 February, 2019)
Anthropologist Manuel João Ramos will be joining us from the University Institute of Lisbon to talk about his parallel life as an illustrator and sketcher and his newly reissued book ‘Of Hairy Kings and Saintly Slaves: An Ethiopian Travelogue’. Tim Ingold has described Manuel’s book in the following glowing terms: ‘Sketchbook in hand, he draws as much as writes, not representing the people and the things he meets, but bringing them irresistibly to life. They explode like crackers from the pages of this book, erupting in a shower of evanescent memories. Why, Ramos asks us, has an anthropology obsessed with visual images forgotten how to draw? And how can drawing and writing be brought together again?’ These are questions which we will be exploring with Manuel. The seminar will be followed by lunch and an optional sketchcrawl on campus – pencils at the ready! The event is free, but please contact Sue Heath (sue.heath@manchester.ac.uk) if you wish to attend as numbers are limited. Followed by optional sketch crawl: 1-3pm. Do feel free to join us for a bit of sketching. No minimum experience/skill and no need to bring special materials.